Gαi is required for carvedilol-induced β1 adrenergic receptor β-arrestin biased signaling. Issue 1 (December 2017) - Wang, Jialu; Hanada, Kenji; Staus, Dean; Makara, Michael; Dahal, Giri; Chen, Qiang; Ahles, Andrea; Engelhardt, Stefan; Rockman, Howard
Abstract The β1 adrenergic receptor (β1 AR) is recognized as a classical Gαs -coupled receptor. Agonist binding not only initiates G protein-mediated signaling but also signaling through the multifunctional adapter protein β-arrestin. Some βAR ligands, such as carvedilol, stimulate βAR signaling preferentially through β-arrestin, a concept known as β-arrestin-biased agonism. Here, we identify a signaling mechanism, unlike that previously known for any Gαs -coupled receptor, whereby carvedilol induces the transition of the β1 AR from a classical Gαs -coupled receptor to a Gαi -coupled receptor stabilizing a distinct receptor conformation to initiate β-arrestin-mediated signaling. Recruitment of Gαi is not induced by any other βAR ligand screened, nor is it required for β-arrestin-bias activated by the β2 AR subtype of the βAR family. Our findings demonstrate a previously unrecognized role for Gαi in β1 AR signaling and suggest that the concept of β-arrestin-bias may need to be refined to incorporate the selective bias of receptors towards distinct G protein subtypes. β1 and β2 adrenergic receptors (ARs) are the predominant G protein-coupled receptor subtypes expressed in mammalian hearts. Here the authors describe a signaling mechanism where the biased agonist carvedilol converts β1AR from a classical Gαs -coupled to a Gαi -coupled receptor to mediate β-arrestin-dependent signaling.